(untitled) (Al-Qamar, 2023)
Women, especially those who are illiterate or pardanashin, are often fall victim to fraudulent practices in property transactions in Pakistan. Despite the Islamic obligations to protect rights of women, they continue to struggle to safeguard their rights and interests. When illiterate or pardanashin women are defrauded, they may turn to the courts for help. However, it is often argued in court that, due to the principle of caveat emptor (let the buyer beware), women should have taken more care during the transactions. Nevertheless, the courts have recognized that Pakistani women still rely on the bonafide of the men around them, such as their brothers, guardians, and husbands. This makes it difficult for women to defend their rights in property transactions. Therefore, it is important to highlight the principles of transactions with pardanashin or illiterate ladies that have been developed by the courts. This research aims to highlight the legal principles and safeguards developed by courts that protect the rights and property of pardanashin or illiterate women. It will also develop recommendations to enhance the protection of their rights and interests in property transactions.